Development of post-quantum cryptosystems based on the Rao-Nam scheme - Melenti, Yevhen; Korol, Olha; Shulha, Volodymyr; Milevskyi, Stanislav; Sievierinov, Оleksandr; Voitko, Oleksandr; Rzayev, Khazail; Husarova, Iryna; Kravchenko, Serhii; Pashayeva, Sevinj (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the research is the process of ensuring the protection of data transmission in communication channels of critical infrastructure objects based on mobile and smart technologies. The development of quantum computing technologies based on Grover and Shor algorithms provides practical cracking of symmetric and asymmetric cryptosystems in polynomial time. The emergence of systems based on artificial intelligence allows creating hybrid systems for detecting weaknesses (critical points) in security systems not only on critical infrastructure objects. In addition, a full-scale quantum computer will open a new era of implementing post-quantum cryptography algorithms. Among the winners of post-quantum algorithms, the crypto-code constructions (CCC) of McEliece and Niederreiter are separately highlighted, which allow to provide the required level of protection and the required level of reliability of information transmission in an integrated manner. But a significant drawback is the possibility of cracking such systems on linear codes, as well as the need to build them on the Galois field 210–213, which significantly reduces their use in low-capacity systems based on smart and mobile technologies. To solve this drawback, the work proposes the use of a symmetric CCC based on the Rao-Nam scheme on algebrogeometric and flawed codes, which provides the possibility of significantly reducing the volume of key data (construction of CCC over the Galois field 24–26). When using the Rao-Nam CCC, a quantum symmetric algorithm is formed, which ensures the preservation of the level of stability and reliability of information transmission (safe time 1025–1035). This approach provides the possibility of forming intelligent information protection systems (IIPS). The given structural scheme of the IIPS construction ensures timely detection of threats with an assessment of the computational and financial and human capabilities of attackers, as well as the use of the necessary CCC/algebraic (flawed) codes to ensure the required level of security